A transdisciplinary approach to address climate change adaptation for human health and well-being in Africa - Wright, Caradee Yael; Moore, Candice Eleanor; Chersich, Matthew; Hester, Rebecca; Schwerdtle, Patricia; Mbayo, Guy Kakumbi; Akong, Charles Ndika; Butler, Colin D. (International journal of environmental research and public health, 2021)
The health sector response to dealing with the impacts of climate change on human health, whether mitigative or adaptive, is influenced by multiple factors and necessitates creative approaches drawing on resources across multiple sectors. This short communication presents the context in which adaptation to protect human health has been addressed to date and argues for a holistic, transdisciplinary, multisectoral and systems approach going forward. Such a novel health-climate approach requires broad thinking regarding geographies, ecologies and socio-economic policies, and demands that one prioritises services for vulnerable populations at higher risk. Actions to engage more sectors and systems in comprehensive health-climate governance are identified. Much like the World Health Organization’s ‘Health in All Policies’ approach, one should think health governance and climate change together in a transnational framework as a matter not only of health promotion and disease prevention, but of population security. In an African context, there is a need for continued cross-border efforts, through partnerships, blending climate change adaptation and disaster risk reduction, and long-term international financing, to contribute towards meeting sustainable development imperatives.
Gesehen am 29.07.2021